Calculation Theory and Test Verification for Skeleton Curve of T-shaped Shear Walls. Issue 2 (1st May 2017) - Liu, Chengqing; Ni, Xiangyong; Wu, Handan; Wei, Xiaodan; He, Bin
Abstract: The moment-curvature skeleton curve of a cross-section, and the force-displacement skeleton curve of shear walls, are both simplified to four lines represented by four reference points: the cracking, yield, peak and ultimate points. Based on traditional flexural theory and flat section assumptions, considering the effect of different axial forces and the influence of the edge constraints in the end-zones on the values of the peak and ultimate points, a theory for calculating the four reference points of the moment-curvature skeleton curve was established. Based on the four reference points of the moment-curvature skeleton curve, a theory for calculating the four reference points of the force-displacement skeleton curve of shear walls was established. This theory considers the influence of shear on the top displacement of shear walls. Based on the equations in this paper, self-made programs were made to obtain the force-displacement skeleton curves precisely. To validate the accuracy of the theory, some examples of analyses in the relevant literature were used to compare the analytical values with the test results, which were found in good agreement. The force-displacement skeleton curve obtained by the calculation theory can be used as a guide for the performance-based seismic design of T-shaped shear walls.